Tomorrow's Internet. (Economist, 1999)
Focuses on the future of the Internet in light of the ruling against Microsoft Corp. in an antitrust trial. Reasons for the assertion that no single company will gain dominance over the Internet, including the use of open standards and the use of public forums; The belief that the Internet will dominate the computer operating system for application development and user interface; Three drawbacks to the Internet.